The Effectiveness of an interactive electronic book in a Unit in The Science course in Developing Visual Thinking Skills and the Enjoyment of Learning Science among fourth grade students - Elazzab, Eman Saber Abdelkader; Elqahtany, Ebtsam Ayied Mansour (Journal of Curriculum and Teaching Methodology, 2023)
The research aimed to investigate the effectiveness of an interactive e-book for the "Environmental Systems" unit in the science course for the fourth grade of primary school in developing visual thinking skills and enjoying learning science. The experimental approach was used for the quasi-experimental design of the experimental and control groups., A female officer studied in the usual way of teaching, and the visual thinking skills test was applied in the dimensions (learned scientific subjects, learning activities, and learning motivation), and the enjoyment of science learning scale in the dimensions (learned scientific subjects, learning activities, and learning motivation)., The results revealed that there were statistically significant differences between the scores of the experimental and control groups in favor of the experimental group on the two research tools.
Keywords: interactive e-book; visual thinking; enjoying learning; science course; primary school students